Missense BICD2 variants in fetuses with congenital arthrogryposis and pterygia - Layla Masuda; Akihiro Hasegawa; Hiromi Kamura; Fuyuki Hasegawa; Michihiro Yamamura; Kosuke Taniguchi; Yuki Ito; Kenichiro Hata; Osamu Samura; Aikou Okamoto (Human Genome Variation)
Abstract Type 2 spinal muscular atrophy with lower extremity dominance (SMALED2) is caused by bicaudal D cargo adaptor 2 (BICD2) variants. However, the SMALED2 genotype and phenotype correlation have not been thoroughly characterized. We identified de novo heterozygous BICD2 missense variants in two fetuses with severe, prenatally diagnosed multiple arthrogryposis congenita. This report provides further insights into the genetics of this rare disease.